100 Years of the American Economic Review: The Top 20 Articles - Arrow, Kenneth J; Bernheim, B. Douglas; Feldstein, Martin S; McFadden, Daniel L; Poterba, James M; Solow, Robert M (American Economic Review, 2011)
This paper presents a list of the top 20 articles published in the American Economic Review during its first 100 years. This list was assembled in honor of the AER's one-hundredth anniversary by a group of distinguished economists at the request of AER's editor. A brief description accompanies the citations of each article.